Learning Mendelian Genetics Using A Game Based Learning Activities - Aliling, Jannah Kristine M.; Aquino, Marylina F.; Arellano, Joanne A.; Zara, Celso G. (International Journal of Basic and Applied Sciences, 2025)
This study aimed to develop and evaluate a game-based learning ‎activity on Mendelian Genetics to improve student engagement, ‎understanding, and motivation. The activity was designed using the ‎ASSURE model, a systematic approach to instructional planning. A ‎mixed-methods design was used. The quantitative phase involved a ‎one-group pre-test and post-test with 45 Grade 8 students from Ilat ‎National High School to assess learning gains. The qualitative phase ‎involved unstructured interviews to explore students’ learning ‎experiences. The game, titled “The Gene Quest: Mendelian ‎Genetics,” featured animations, interactive Punnett square tasks, ‎and a leaderboard to enhance participation. Six experts—four ‎science teachers and two IT professionals—evaluated the game ‎based on content accuracy, design, usefulness, and ease of use. Data ‎collection tools included a 30-item multiple-choice test, expert ‎evaluation sheets, and interview responses. Quantitative data were ‎analyzed using weighted and composite means and the Hake gain ‎score, while thematic analysis was used for qualitative data. The ‎game received excellent ratings across all evaluation criteria. A Hake ‎gain score of 0.96 indicated a high level of learning improvement. ‎Students described the game as enjoyable and engaging. They ‎reported better understanding of genetics concepts, improved ‎confidence in learning, and acknowledged certain challenges during ‎gameplay. The findings suggest that game-based learning is an ‎effective strategy for teaching complex topics like Mendelian ‎Genetics. It supports deeper understanding, boosts motivation, and ‎enhances academic performance‎.
Keywords: Game-Based Learning Activities; ‎Mendelian Genetics; ‎ Gamification; ‎ Learning Gain; ‎ Grade 8 Science‎.